SOLUTION OF SHARIAH ECONOMIC DISPUTES IN THE PROVISIONS SET BY THE SUPREME COURT - Rifqi Azis Amrullah (JESKaPe: Jurnal Ekonomi Syariah, Akuntansi dan Perbankan, 2022)
Increase users of sharia contracts is directly proportional to the increase in sharia economic disputes. The occurrence of disputes can be caused by one party breaking a contract or committing an unlawful act. In the event of a dispute, the party who feels aggrieved can submit a lawsuit to the court, but it turns out that during the examination of the case the judge found that the contract used was deemed not in sharia complience, while none of the parties filed a lawsuit for cancellation the contract. In this study, the authors used normative juridical research methods. by exploring the provisions of the supreme court which serve as guidelines for judges in examining cases of sharia economic disputes, while also using a conceptual approach by looking at Islamic law concepts regarding inappropriate contracts. with Islamic law. In this study the authors conclude that there are still many legal voids governing sharia economics, the existing provisions only regulate in general and universally, even contradicting each other. As a result of this legal vacuum, the supreme court made rules for examining sharia economic cases, where in several provisions found inconsistencies in the regulations made, or even contradicting each other, so it is necessary for judges to carry out ijtihad and decide on cases that are demanded by the parties in order to fulfill the principle of divinity. and so that the decision remains on the provisions stipulated by Islamic law